VIRTUAL EDUCATIONAL PLATFORMS FROM THE POINT OF VIEW OF FACULTY MEMBERS AT IMAM ABDUL RAHMAN BIN FAISAL UNIVERSITY (EVALUATION STUDY) - Dr. Sherin Hassan Mabrouk, Dr.Rania Mohammed Abdul Jawad, Reema Mahmoud AlOqlah, Ms Lamyaa Mohamed Badr Ali, Ms Sayequa Shujauddin Dandoti (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study aimed to identify the reality of using the virtual educational platforms Blackboard at Imam Abdul Rahman bin Faisal University, from the viewpoint of the faculty members. The descriptive approach was used, and a questionnaire was designed to collect data, and after the verification process was conducted, it was distributed to a random sample of (65) members representing the study population in the Deanship of the preparatory year. Imam Abdul Rahman bin Faisal; The lack of statistical significance between the responses of the sample members from the Imam Abdul Rahman bin Faisal University professors about the reality of using the blackboard virtual educational platforms due to the variables of experience and specialization, in addition to the presence of some difficulties preventing the use of the virtual electronic educational platforms Blackboard at Imam Abdul Rahman bin Faisal University. In light of this, the study recommended encouragement and awareness of Imam Abdul Rahman bin Faisal University, to take advantage of the technology of the virtual electronic educational platforms Blackboard, in order to facilitate and improve the educational learning practice, especially in the field of virtual electronic educational platforms Blackboard.